PENINGKATAN KREATIVITAS BERPIKIR SISWA DALAM IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN PAI - Titin Anggraini; Saidil Mustar; Dini Palupi Putri (Al-Mau'izhoh, 2020)
This study aimed to find out a depiction of the implementation of the 2013 curriculum and its relationship with the efforts to improve students' creative thinking. This study used a qualitative approach. Data were obtained from observation and interview techniques. This study concluded that the 2013 curriculum, in all state schools, needs to continue to encourage the realization of national standard fulfillment. Preparation of learning plans and programs (Syllabus, LP: Lesson Plan) were already carried out; the explanations of learning materials were already delivered with various supporting media and methods; and learning resources were adequate such as textbooks and worksheets.Keywords: Creative Thinking, Implementation, 2013 Curriculum